Mass‐produced graphene—HDPE nanocomposites: Thermal, rheological, electrical, and mechanical properties. Issue 4 (8th November 2018) - Batista, Natassia L.; Helal, Emna; Kurusu, Rafael S.; Moghimian, Nima; David, Eric; Demarquette, Nicole R.; Hubert, Pascal
Abstract : Economically viable high‐density polyethylene (HDPE)/graphene nanocomposites were produced using mass produced graphene powder and an industrial twin‐screw melt‐compounding machine. Rheological and electrical properties were investigated and scanning electron microscopy was carried out to investigate graphene dispersion and its network formation in the matrix. Mechanical properties of the nanocomposites were evaluated using tensile, flexural and impact tests. Differential scanning calorimetry analysis indicated that the crystalline structure of the polymer might be affected by high loadings of graphene. SEM evaluation revealed reasonable graphene dispersion in the matrix. In addition, the amount of graphene required to form a percolated network was similar for both rheological and electrical networks. The nanocomposites exhibited a significant increase in Young's and flexural moduli without a notable reduction in impact strength up to 14 wt% graphene loading. In these experiments, compounding graphene powder with HDPE produced a clear and distinct improvement in mechanical properties at an industrially suitable low cost. POLYM. ENG. SCI., 59:675–682, 2019. © 2018 Society of Plastics Engineers